Xeno-Free Strategies for Safe Human Mesenchymal Stem/Stromal Cell Expansion: Supplements and Coatings - M. Cimino; R. M. Gonçalves; C. C. Barrias; M. C. L. Martins (Stem Cells International)
Human mesenchymal stem/stromal cells (hMSCs) have generated great interest in regenerative medicine mainly due to their multidifferentiation potential and immunomodulatory role. Although hMSC can be obtained from different tissues, the number of available cells is always low for clinical applications, thus requiring in vitro expansion. Most of the current protocols for hMSC expansion make use of fetal bovine serum (FBS) as a nutrient-rich supplement. However, regulatory guidelines encourage novel xeno-free alternatives to define safer and standardized protocols for hMSC expansion that preserve their intrinsic therapeutic potential. Since hMSCs are adherent cells, the attachment surface and cell-adhesive components also play a crucial role on their successful expansion. This review focuses on the advantages/disadvantages of FBS-free media and surfaces/coatings that avoid the use of animal serum, overcoming ethical issues and improving the expansion of hMSC for clinical applications in a safe and reproducible way.